Membangun ekosistem digital UMKM di era pandemi COVID-19 melalui PT PII (Persero) di, Kuningan Barat, Jakarta - Indra Pradana Singawinata; Muhammad Saifulloh (Jurnal Pustaka Dianmas, 2021)
The problem of Micro, Small and Medium Enterprises (MSMEs) during the crisis has problems as well as challenges in the midst of the Covid-19 pandemic crisis. One of the problems faced by business actors is the problem of capital and using digital technology. Capital is the main factor so that the business continues to run smoothly. However, in this digitalization era, the use of digital technology is also a problem when marketing products due to competition and reaching an increasingly complex and increasing market. But currently, MSMEs are one of the sectors in the economy in Indonesia that have a very important role. It has a large potential in driving economic activities and becomes the source of income for the majority of the population, as well as absorbing workers with low education and running in small business activities, both traditional and modern. With this training, it will further strengthen the position and gain benefits for MSME players both now and in the future.